Electronic, optical and thermoelectric investigations of Zintl phase AE3AlAs3 (AE = Sr, Ba): First-principles calculations - Bekhti-Siad, Amara; Bettine, K.; Rai, Dibya Prakash; Al-Douri, Yarub; Wang, Xiaotian; Khenata, Rabah; Bouhemadou, Abdelmadjid; Voon, Chun Hong (Elsevier, 2018)
First principles calculations were performed to investigate the electronic, optical and thermoelectric properties of Zintl orthorhombic phase AE3AlAs3 (AE = Sr, Ba) compounds using the full potential linearized augmented plane wave method. The exchange-correlation potential is treated with the generalized gradient approximation (GGA) and modified Becke-Johnson potential (TB-mBJ) to improve the electronic structure calculations. These two compounds are semiconductors have direct band gaps. The optical transitions are investigated via dielectric function along with other related optical constants such as refractive index and absorption coefficient. Thermoelectric properties are examined using the combination of electronic structure and Boltzmann transport theory. In detail, the calculated results of Seebeck coefficient, electrical and thermal conductivity, figure of merit and power factor are reported as a function of temperature.